Battery diaphragm with high-heat-resistance ceramic coating and preparation method of battery diaphragm
By applying a three-dimensional structure formed by high-density inorganic ceramic powder on the lithium battery separator, the problem of insufficient stability of the existing separator at high temperature is solved, and higher thermal stability and safety performance are achieved, which meets the high temperature environment. Battery safety requirements.
Patent Information
- Application Number
- CN202411322911.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-27
AI Technical Summary
The existing lithium battery separators are difficult to maintain stability in high temperature environments, resulting in safety problems. The existing heat resistance performance is insufficient and cannot meet the needs of high-power and high-energy-density electronic products.
Using a high heat-resistant ceramic coating battery separator, the base film is coated with inorganic ceramic powder and binder with a density of 5-15g/cm3 to form a rigid framework with a three-dimensional structure, which resists the movement of the internal molecular chain of the membrane under high temperature environment. resulting in stress release and large-area shrinkage.
It effectively prevents the diaphragm from shrinking and melting under thermal runaway conditions, improves the thermal stability and safety performance of the diaphragm, and meets the dimensional stability requirements in high temperature environments above 220℃.
Smart Images

Figure CN119208915A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery manufacturing, and in particular to a battery separator with a high heat-resistant ceramic coating and a preparation method thereof, so as to improve the electrochemical performance and safety performance of a lithium battery Background Art
[0002] With the large-scale application of power batteries and energy storage batteries in life, their safety issues have received more and more attention. As a key material affecting battery safety, the requirements and expectations for the safety of diaphragms are also continuously increasing. In addition, domestic and foreign battery companies are seeking 220-300℃ A diaphragm whose dimensions remain stable under temperature conditions.
[0003] At present, the market mainly uses alumina or boehmite coated on polyolefin microporous membranes to improve the heat resistance of the membrane, but with the high demand for heat resistance of high-power and high-energy density electronic products, this type of membrane is difficult to meet market demand. Therefore, it is urgent to develop high-temperature resistant membranes, such as those that still show high-temperature thermal stability at 220°C. Summary of the invention
[0004] The purpose of the present invention is to solve the high temperature thermal stability of the diaphragm. The existing production technology is insufficient in heat resistance, which easily leads to safety problems. The thermal stability of the diaphragm achieved by the present invention can improve safety. Specifically, the base film has internal stress due to traction and stretching during the preparation process. Under high temperature environment, the stress is released due to the movement of the molecular chains inside the diaphragm, resulting in large-area shrinkage. Another purpose of the present invention is to provide a method for preparing a high-heat-resistant ceramic coated battery diaphragm.
[0005] To achieve the above object, the present invention provides a battery separator with a high heat-resistant ceramic coating, characterized in that the battery separator comprises a base film and a ceramic coating coated thereon, wherein the ceramic coating comprises ceramic powder and a binder, and the binder bonds the ceramic powder to the base film; the ceramic powder further comprises at least one inorganic substance A, and its density is 5-15 g / cm 3 .
[0006] Preferably, the ceramic powder further comprises at least one having a density of 0.1-5 g / cm 3 The inorganic particles make the average density of the ceramic powder be 1-15g / cm 3 , wherein the density of the inorganic substance A is greater than that of the inorganic particles.
[0007] Preferably, the inorganic particles include titanium oxide, aluminum hydroxide, magnesium hydroxide, aluminum oxide, boehmite, magnesium oxide, calcium oxide, beryllium oxide, or any combination thereof.
[0008] Preferably, the inorganic substance A includes barium titanate, cerium oxide, zirconium dioxide, yttrium oxide, or any combination thereof.
[0009] Preferably, the ceramic coating is coated on one side or both sides of the base film, and the ratio of ceramic powder and binder contained in each ceramic coating is the same or different.
[0010] Preferably, the ceramic powder has a particle size of 0.05 μm to 2 μm and a specific surface area of 1 to 200 m 2 / g.
[0011] Preferably, the inorganic material A has a particle size of 0.05 μm-2 μm and a specific surface area of 1 to 200 m 2 / g.
[0012] Preferably, the mass ratio of the inorganic substance A to the ceramic powder is 1:(1-100).
[0013] A method for preparing a battery separator with a high heat-resistant ceramic coating, characterized in that it comprises: Next steps:
[0014] S1: Add the dispersant into deionized water and stir well to obtain a dispersant solution.
[0015] S2: adding ceramic powder containing at least one inorganic substance A into the dispersant solution and continuing to stir, and then adding into a grinder for dispersion.
[0016] S3: sequentially adding a thickener, a binder and a wetting agent into the mixture ground in step S2 and stirring the mixture evenly, and then performing demagnetization filtration to obtain a coating slurry.
[0017] S4: coating the coating slurry obtained in step S3 on the base film, and then drying it to obtain a diaphragm with a coating layer.
[0018] Preferably, the mass ratio of the inorganic substance A to the ceramic powder is 1:(1-100).
[0019] Preferably, the ceramic powder D50 particle size is 0.05 μm-2 μm; the inorganic substance A The particle size is 0.05μm-2μm.
[0020] The present invention provides a battery separator with a high heat-resistant ceramic coating and a preparation method thereof, which has a beneficial effect in that the ceramic material is distributed in the three-dimensional structure of the separator to form a specific rigidity. The skeleton, with its rigid support, can effectively Prevent the diaphragm from shrinking under thermal runaway conditions,Melting. When we apply a ceramic coating containing at least one inorganic substance A with a high density on the base film, due to its large gravity, it can play the role of a "pillar" in the three-dimensional structure of the diaphragm, forming a more stable rigid structure, thereby resisting the stress release caused by the movement of the molecular chains inside the diaphragm in a high temperature environment, resulting in large-scale shrinkage. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a schematic diagram illustrating the state of the ceramic coating and base film after high temperature.
[0022] Figure 2 It is a flow chart illustrating the preparation process of the present invention. DETAILED DESCRIPTION
[0023] In order to make the above and / or other purposes, effects, and features of the present invention more clearly understood, preferred embodiments are specifically described below in detail:
[0024] See also Figure 1 The present invention provides a battery separator with a high heat-resistant ceramic coating, which comprises a base film (2) and a ceramic coating (1); the ceramic coating (1) comprises a ceramic powder (12) and a binder, and the binder bonds the ceramic powder (12) to the base film (2); the ceramic powder (12) further comprises at least one inorganic substance A (11) having a density of 5-15 g / cm 3 .
[0025] In some embodiments, the inorganic substance A (11) comprises barium titanate, cerium oxide, zirconium dioxide, yttrium oxide, or any combination thereof; the particle size is 0.05 μm-2 μm, preferably 0.1-1 μm; density is 5-15g / cm 3 , preferably with a density of 5-10 g / cm 3 ; Specific surface area is 1-200m 2 / g, Preferably 1-100m 2 / g.
[0026] In some embodiments, the ceramic powder (12) further comprises at least one material having a density of 0.1-5 g / cm 3 The inorganic particles make the ceramic powder (12) have an average density of 1-15 g / cm 3 , wherein the density of the inorganic substance A is greater than that of the inorganic particles.
[0027] In some embodiments, the inorganic particles include titanium oxide, aluminum hydroxide, magnesium hydroxide, aluminum oxide, boehmite, magnesium oxide, calcium oxide, beryllium oxide, or any combination thereof. The total mass ratio of the ceramic powder (12) to deionized water is 1: (1.25-10), i.e., 10% to 80%; the ceramic powder (12) The particle size D50 is 0.05 μm-2 μm, preferably 0.1-1 μm; the average density of the ceramic powder (12) is 1-15 g / cm 3 , preferably 2-10g / cm 3 The ceramic powder (12) has an average specific surface area of 1 to 200 m 2 / g, preferably 1-100m 2 / g.
[0028] In some embodiments, the ceramic coating (1) is coated on one side or both sides of the base film (2), and the ceramic powder (12) and the binder contained in each ceramic coating (1) are the same or different.
[0029] In some embodiments, the base film (2) used includes a polyethylene microporous film, a polypropylene microporous film or a polypropylene / polyethylene composite microporous film, and the base film (2) has a thickness of 3 to 20 μm, preferably 5 to 14 μm, and an air permeability of 30 to 300 s / 100 cc.
[0030] In some embodiments, the coating thickness is 0.5 μm to 7 μm, preferably 0.5-4 μm.
[0031] In some embodiments, the total mass ratio of the inorganic substance A (11) to the ceramic powder (12) is 1:(1-100), that is, the inorganic substance A (11) accounts for 1% to 100% of the mass of the ceramic powder (12), preferably 50% to 100%.
[0032] Preparation method
[0033] A method for preparing a battery separator having a high heat-resistant ceramic coating (1), the method comprising: Next steps: S1: adding a dispersant to deionized water and stirring well to obtain a dispersant solution; S2: will contain at least one density of 5-15g / cm 3 Ceramic powder (12) of inorganic substance A (11) is added Add to the dispersant solution and continue stirring, then add to the grinder for dispersion; S3: adding a thickener, a binder, and a wetting agent to the mixture ground in step S2 in sequence, stirring evenly, and then performing magnetic removal and filtration to obtain a coating slurry; S4: coating the coating slurry obtained in step S3 on the base film (2), and then drying to obtain a diaphragm with a coating layer; the coating is performed using a wire rod, a groove roller, etc.
[0034] In some embodiments, in step S1, the dispersant is at least one of polyethylene glycol, sodium polyacrylate, polypropylene, polyethylene, polyvinylpyrrolidone, ammonium polyacrylate, and sodium hexametaphosphate; the total mass ratio of the dispersant to the ceramic powder (12) is 1:(50-2000).
[0035] In some embodiments, in step S2, the ceramic powder (12) further comprises at least one material having a density of 0.5-15 g / cm 3 The inorganic particles make the ceramic powder (12) have an average density of 1-15 g / cm 3 , preferably 2-10g / cm 3 , wherein the density of the inorganic substance A is greater than that of the inorganic particles.
[0036] In some embodiments, in step S3, the binder includes polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl alcohol, polyacrylic acid, polyacrylonitrile and polyacrylate, polyacrylamide, melamine, styrene-butadiene rubber, phosphates, silicates, lignin, polyimide, or any combination thereof; the total mass ratio of the binder to the ceramic powder (12) is 1:(5-100).
[0037] In some embodiments, in step S3, the thickener includes sodium carboxymethyl cellulose, methyl cellulose, hydroxypropyl methyl cellulose, carbomer resin, or any combination thereof; the total mass ratio of the thickener to the ceramic powder (12) is (0.1-2):100.
[0038] In some embodiments, in step S3, the wetting agent includes organic modified silicon oxides, polyols, fatty alcohol ethers, or any combination thereof. The ratio of the wetting agent to the total mass of the ceramic powder (12) is (0.01-2):100.
[0039] In some embodiments, in step S4, the coating method is one of gravure printing, doctor blade coating, extrusion coating or wire rod coating; the coating location is any one side or both sides of the base film (2).
[0040] In some embodiments, in step S4, the base film (2) coated with the coating slurry is dried. The drying method is preferably oven drying. The drying temperature is 40 to 150° C. and the drying time is 0.01 h to 0.5 h.
[0041] The slurry preparation methods provided in this application are all implemented at room temperature, are simple to operate, and are easy to scale up.
[0042] Example 1
[0043] A method for preparing a high heat-resistant ceramic coating battery separator, the preparation method is as follows:
[0044] Step 1: Weigh 0.5 g of sodium polyacrylate and dissolve it in 100 g of deionized water. Use an overhung stirrer to stir at 1000 r / min for 1 hour to form a dispersant aqueous solution.
[0045] Step 2: Place 10 g of barium titanate (density 6 g / cm 3 , the specific surface area is 3.4m 2 / g) was added to the dispersant aqueous solution and stirred at 2000r / min for 1h using an overhung stirrer. Then 90g of alumina (density 4g / cm 3 , the specific surface area is 7.5m 2 / g) was added into the dispersant aqueous solution, stirred at 2000 r / min for 1 h using an overhead stirrer, and then ground.
[0046] Step 3: Add 3g sodium carboxymethyl cellulose aqueous solution, stir for 30 minutes, then add 10g The acrylic emulsion was stirred at 300 r / min for 1 h using a cantilever stirrer. After being evenly dispersed, 0.05 g of a silicone surface additive was added and stirred at 300 r / min for 1 h using a cantilever stirrer to obtain a uniform slurry.
[0047] Step 4: Use a coating machine to apply the slurry to one side of a polyethylene film with a thickness of 9 μm, dry it in a 60°C oven for 3 minutes, and the coating thickness after drying is 2 μm, to obtain a single-sided coated separator. Use a coating machine to apply the slurry to the other side of the polyethylene film, dry it in a 60°C oven for 3 minutes, and the coating thickness after drying is 2 μm, to obtain a double-sided 4 μm coated separator.
[0048] Example 2
[0049] This embodiment provides a method for preparing a high heat-resistant ceramic coated battery separator. The difference between Example 2 and Example 1 is that in step 2, the amount of barium titanate powder added is 30 g, and the amount of aluminum oxide added is 70 g.
[0050] Example 3
[0051] This embodiment provides a method for preparing a high heat-resistant ceramic coated battery separator. The difference between Example 3 and Example 1 is that in step 2, the amount of barium titanate powder added is 50 g, and the amount of aluminum oxide added is 50 g.
[0052] Example 4
[0053] This embodiment provides a method for preparing a high heat-resistant ceramic coated battery separator. The difference between Example 4 and Example 1 is that in step 2, the amount of barium titanate powder added is 70 g, and the amount of aluminum oxide added is 30 g.
[0054] Example 5
[0055] This embodiment provides a method for preparing a high heat-resistant ceramic coated battery separator. The difference between Example 5 and Example 1 is that in step 2, the amount of barium titanate powder added is 90 g, and the amount of aluminum oxide added is 10 g.
[0056] Example 6
[0057] This embodiment provides a method for preparing a high heat-resistant ceramic coated battery separator. The difference between Example 6 and Example 1 is that in step 2, the amount of barium titanate powder added is 100 g, and the amount of aluminum oxide added is 0 g.
[0058] Example 7
[0059] This embodiment provides a method for preparing a high heat-resistant ceramic coating battery separator. The difference between Example 7 and Example 1 is that the amount of barium titanate powder added in step 2 is 30g, and alumina is replaced by boehmite (density 3g / cm 3 ), the added amount is 70g.
[0060] Comparative Example 1
[0061] To compare the effect of barium titanate on improving the heat resistance of the diaphragm, the difference between Comparative Example 1 and Example 1 is that the amount of barium titanate powder added in step 2 is 0 g, and the amount of aluminum oxide added is 100 g.
[0062] Comparative Example 2
[0063] To compare the effect of barium titanate on improving the heat resistance of the diaphragm, the difference between Comparative Example 2 and Example 1 is that in step 2, the barium titanate powder is replaced with boehmite, the addition amount is 30g, and the addition amount of aluminum oxide is 70g.
[0064] Comparative Example 3
[0065] To compare the effect of barium titanate on improving the heat resistance of the diaphragm, the difference between Comparative Example 3 and Example 1 is that in step 2, the barium titanate powder is replaced with boehmite, the addition amount is 50g, and the addition amount of aluminum oxide is 50g.
[0066] Comparative Example 4
[0067] To compare the effect of barium titanate on improving the heat resistance of the diaphragm, the difference between Comparative Example 4 and Example 1 is that in step 2, the barium titanate powder is replaced with boehmite, the addition amount is 70g, and the addition amount of aluminum oxide is 30g.
[0068] Comparative Example 5
[0069] In order to compare the effect of barium titanate on improving the heat resistance of the diaphragm, the difference between Comparative Example 5 and Example 1 is that the barium titanate powder in step 2 is replaced with boehmite, the addition amount is 90g, and the addition amount of aluminum oxide is 10g.
[0070] [Coating average unit surface density test]
[0071] Test method: Cut three pieces of diaphragms with a size of 40mm*60mm in the MD*TD direction of the base film and the ceramic coating film. First, put the three pieces of base film into the analytical balance and weigh them to obtain m1, m2, m3, and then use a thickness gauge to measure the thickness of the three base films to be h1, h2, and h3; similarly, The three ceramic coating films were weighed in an analytical balance to obtain m4, m5, and m6, and then the thickness of the three ceramic coating films was measured by a thickness gauge to obtain h4, h5, and h6. According to the calculation formula, the average surface density ρ = (m1 + m2 + m3) / 3 / 0.0024, the average surface density of the base film was calculated to be ρ1, and the average surface density of the ceramic coating film was calculated to be ρ2. Since the average thickness of the coating h is (h4 + h5 + h6) / 3 - (h1+h2+h3) / 3, so the final calculated average unit surface density of the coating is ρ=(ρ2-ρ1) / h.
[0072] [Heat shrinkage test]
[0073] Test method: Cut 6 ceramic coated membranes with a size of 60mm*40mm in MD*TD direction, and pierce 2 small holes in the MD and TD directions at the same position of all ceramic coated membranes, and measure the hole spacing in the MD direction as d1, and the hole spacing in the TD direction as d2. Divide the 6 coated membranes into 2 groups, place them on 10 A4 papers respectively, and press 10 A4 papers on the coated membranes, fix them with paper clips, put one group in a constant temperature oven at 150℃, and put the other group in a constant temperature oven at 220℃ for 1h, and finally measure the hole spacing in the MD and TD directions of the heated membranes, which are d3 and d4 respectively, and finally calculate the thermal shrinkage rate of the membrane in the MD direction p=(d1-d3) / d1*100%, and the thermal shrinkage rate in the TD direction p=(d2- d4) / d2*100%.
[0074] [Hot nail test]
[0075] Test method: Cut a ceramic coating film with a diameter of 50mm, fix it on the test mold of the hot nail penetration tester with a fixing clip, and try to keep the surface flat and the force uniform; select a hot nail with a pointed corner diameter of 0.2mm, set the temperature to 250℃, set the distance to -0.1mm, run the program, and after the test is completed, observe and analyze the shape and size of the black spots or holes pierced through the diaphragm under a digital microscope.
[0076] The coated diaphragms prepared in Examples 1-7 and Comparative Examples 1-5 were subjected to performance tests, and the test results are shown in Table 1 below:
[0077] According to Table 1, we can see that:
[0078] From Examples 1-6, it can be found that as the ratio of inorganic substance A to ceramic powder increases, the average unit surface density of the coating increases, and the thermal shrinkage of the diaphragm at 150°C and 220°C decreases accordingly, and the thermal shrinkage at 150°C is <3%; the membrane rupture diameter of the hot nail puncture test also decreases accordingly.
[0079] By comparing the results of Examples 1-7 and Comparative Examples 1-5, it can be seen that adding inorganic substance A to the ceramic powder can significantly improve the thermal shrinkage of the separator and reduce the diameter of the membrane ruptured by thermal puncture, thereby improving the safety of the battery.
[0080] By comparing the results of Example 7 and Comparative Examples 1-2, it can be seen that by adding inorganic substance A to the ceramic powder, even if the average unit surface density of the coating of Example 7 is less than that of Comparative Examples 1-2, the thermal shrinkage rate of the diaphragm can be significantly improved, and the diameter of the ruptured membrane caused by thermal puncture can be reduced, thereby improving the safety of the battery.
[0081] However, what is described above is only a preferred embodiment of the present invention, but it cannot be used to limit the patent protection scope of the present invention; therefore, all simple equivalent changes and modifications made according to the patent protection scope of the present invention and the contents of the specification still fall within the patent protection scope of the present invention.
Claims
1. A battery separator with a high heat-resistant ceramic coating, characterized in that: The battery separator comprises a base film and a ceramic coating coated thereon, wherein the ceramic coating comprises ceramic powder and a binder, the binder binds the ceramic powder to the base film, and the ceramic powder comprises at least one inorganic substance A, and its density is 5-15 g / cm 3 .
2. The battery separator according to claim 1, characterized in that: The ceramic powder further comprises at least one density of 0.1-5 g / cm 3 The inorganic particles make the average density of the ceramic powder be 1-15g / cm 3 , wherein the density of the inorganic substance A is greater than that of the inorganic particles.
3. The battery separator according to claim 2, characterized in that: The inorganic particles include titanium oxide, aluminum hydroxide, magnesium hydroxide, aluminum oxide, boehmite, magnesium oxide, calcium oxide, beryllium oxide, or any combination thereof.
4. The battery separator according to claim 1, characterized in that: The inorganic substance A includes barium titanate, cerium oxide, zirconium dioxide, yttrium oxide, or any combination thereof.
5. The battery separator according to claim 1, characterized in that: The ceramic coating is coated on one side or both sides of the base film, and the ceramic powder and the binder contained in each ceramic coating are the same or different in proportion.
6. The battery separator according to claim 1, characterized in that: The ceramic powder has a particle size of 0.05 μm to 2 μm and a specific surface area of 1 to 200 m 2 / g.
7. The battery separator according to claim 1, characterized in that: The inorganic substance A has a particle size of 0.05 μm-2 μm and a specific surface area of 1 to 200 m 2 / g.
8. The battery separator according to claim 1, characterized in that: The mass ratio of the inorganic substance A to the ceramic powder is 1:(1-100).
9. A method for preparing a battery separator with a high heat-resistant ceramic coating, characterized in that: The following steps are involved: S1: adding a dispersant to deionized water and stirring well to obtain a dispersant solution; S2: will contain at least one density of 5-15g / cm 3 The ceramic powder of inorganic substance A is added into the dispersant solution and stirred continuously, and then added into the grinder for dispersion; S3: adding a thickener, a binder, and a wetting agent to the mixture ground in step S2 in sequence and stirring the mixture evenly, and then performing demagnetization filtration to obtain a coating slurry; S4: coating the coating slurry obtained in step S3 on the base film, and then drying it to obtain a diaphragm with a coating layer.
10. The preparation method according to claim 9, characterized in that: The mass ratio of the inorganic substance A to the ceramic powder is 1:(1-100).
11. The preparation method according to claim 9, characterized in that: The particle size of the ceramic powder D50 is 0.05 μm-2 μm, and the particle size of the inorganic substance A is 0.05 μm-2 μm.
Citation Information
Patent Citations
Ceramic diaphragm and preparation method therefor
CN106935778A
Ceramic coating battery diaphragm capable of improving battery capacity and preparation method thereof
CN114447521A
Coating slurry of battery diaphragm, preparation method of coating slurry, battery diaphragm and lithium ion battery
CN115117559A
